Preparation and Characterization of a New High-Performance Plastic Explosive in Comparison with Traditional Types - Ahmed Elbeih; Tamer Elshenawy; Hany Amin; Ahmed K. Hussein; Sara M. Hammad (International Journal of Chemical Engineering)
EPX-2R is a high-performance plastic explosive produced for different applications. EPX-2R is based on RDX (1,3,5-trinitro-1,3,5-triazinane) bonded by the elastic matrix of the softened styrene butadiene binder. A computerizing mixer plastograph was used for the production of EPX-2R. The internal energy of combustion was measured and used to determine the enthalpy of formation. Friction and impact sensitivities were measured. The velocity of detonation was determined experimentally, and the detonation properties were calculated by the EXPLO 5 code. For comparison, traditional plastic explosives, composition C-4, Semtex 10, Formex P1, EPX-1, and Sprängdeg m/46, were studied. It was concluded that the velocity of detonation of EPX-2R was higher than the studied samples except composition C-4, while its sensitivity is the lowest. Interesting inversely proportional relationship between the measured internal energy of combustion and the calculated heat of detonation was observed.